Translation, Cultural Adaptation, and Psychometric Properties of the Danish Version of the Anti-Clot Treatment Scale - Comuth, Willemijn J.; Lauridsen, Henrik H.; Kristensen, Steen D.; Münster, Anna-Marie B. (TH Open, 2018)
Background The Anti-Clot Treatment Scale (ACTS) is a 17-item, 2-factor (Burdens and Benefits), patient-reported outcome instrument to evaluate patient satisfaction with oral anticoagulant treatment.Objectives This study aimed to translate and culturally adapt the English version of the ACTS into Danish and to subsequently validate the Danish version in a population of patients treated with dabigatran etexilate for atrial fibrillation.Methods The ACTS was translated into Danish and culturally adapted. This prospective phase 4 study included 232 respondents who completed the Danish ACTS after 1 month of treatment with dabigatran etexilate for atrial fibrillation. Psychometric properties were evaluated. For test–retest reliability, the ACTS was measured twice, 2 weeks apart, in a subgroup of 50 stable patients.Results Generally, a high level of treatment satisfaction was found. Confirmatory factor analysis showed a suboptimal fit for the two-factor model of the original version. Using modification indices of confirmatory factor analysis, a four-factor model had the best fit. Cronbach's α for internal consistency was acceptable at 0.78. There was good test–retest reliability with intraclass correlation at 0.80. Smallest detectable changes (SDCs) for individual patients were 5.89 points for the total ACTS, 5.57 for the reverse Burdens, and 3.34 for Benefits scores. Group SDCs were 0.39, 0.37, and 0.22 respectively. Substantial ceiling effects limit the ability to detect improvement at the high end of the scale.Conclusion The Danish version of the ACTS has inadequate structural validity. Reliability was acceptable. Ceiling effects challenge detection of improvement of treatment satisfaction in clinical practice in this patient population.
Keywords: atrial fibrillation; cardiology; psychological distress; thrombosis